Age-related changes of elements in renal arteries of Thai and Japanese and the relationships among elements - Pasuk Mahakkanukrauh (2018)
To examine whether there were differences between races in regard to age-related changes of elements and the relationships among elements in the arteries, the authors investigated both the renal arteries of Thai and Japanese. The Thai subjects consisted of 27 men and 11 women, ranging in age from 27 to 88 yr, whereas the Japanese subjects consisted of 19 men and 26 women, ranging in age from 61 to 99 yr. After the ordinary dissections at Chiang Mai University and Nara Medical University were completed, the bilateral renal arteries were resected and the element contents were determined by inductively coupled plasma-atomic emission spectrometry. In the Thai, a slight accumulation of calcium and phosphorus occurred in the fifties, but thereafter hardly increased. In contrast, in the Japanese, an accumulation of calcium and phosphorus began to occur in the seventies and increased markedly in the eighties. The result revealed that a higher accumulation of calcium and phosphorus occurred in the renal arteries of the Japanese in old age compared with those of the Thai. Regarding the relationships among elements, extremely or very significant direct correlations were found among the contents of calcium, phosphorus, magnesium, and sodium in both the renal arteries of the Thai and Japanese, except for magnesium and sodium contents in the renal arteries of the Thai. © Copyright 2005 by Humana Press Inc. All rights of any nature, whatsoever, reserved.